A relação do desempenho motor em testes de campo e em situação de jogo no futebol - Rocha, Paulo Ricardo Higassiaraguti [UNESP] (2015)
Technical skills are critical to the success of a team in soccer. Several studies have used isolated from the game context technical skills tests to identify talented players in soccer and differentiate high level players from those of lower level ones. Researchers stress out that testing technical skills can be used to select potential players to play at high levels. However, there is no conclusive evidence on the relationship between the performance shown by the players in a test battery and the performance of the players in a match. The purpose of this study was to examine the performance of soccer players by a battery of tests involving technical skill and performance of these skills during a match. Were selected for the study 36 players of two teams participating in the U-17 in Campeonato Paulista de Futebol 2014. The assessment of technical skills outside the match context was performed by the F-MARC tests. The performance analysis of the players in the match e was held at Soccer Player Assessment Instrument (SPAI). In this study, IAJF had its content validated because it received the minimum acceptable concept (3 of 5) from all experts. Furthermore, SPAI was validated in its intra and inter examiner reliability, with the Spearman's correlation coefficient results (> 0.60) and Kappa agreement ranging from good (0.61 to 0.80) and excellent (0.81 1.0). The performance of players between the two teams in the F-MARC tests showed no significant difference in any of the them. Finally, the results indicated that there is no relationship between performance on specific tests of technical skill and the performance of these skills during a match. In short, the results of this study suggest that the motor evaluation of players who are training to become professional through batteries of tests little expresses the technical skills performed during a match